2020
DOI: 10.1111/odi.13377
|View full text |Cite
|
Sign up to set email alerts
|

Mouth breathing impairs the development of temporomandibular joint at a very early stage

Abstract: Objectives The study aimed to explore the effects of mouth breathing and hypoxia on the condyle of temporomandibular joint (TMJ) via two animal models. Methods 24 four‐week‐old rats were randomly separated into three groups, consisting of eight control rats, eight intermittent hypoxia (IH) rats, and eight intermittent nasal obstruction (INO) rats. We use the IH model and the INO model to simulate children suffering from hypoxia and mouth breathing. After 16 days, the condyle of TMJ and surrounding white adipos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 40 publications
(41 reference statements)
0
6
0
1
Order By: Relevance
“…In an intermittent nasal congestion rat model, there was a significant reduction in the thickness of the hyperplasia layer as well as the hypertrophic layer of condylar joint, which suggested that the development of the temporomandibular joint was also influenced by oral breathing habits ( 63 ). A previous randomized controlled trial ( 64 ) established another bilateral rat model of intermittent nasal congestion, and it found that mouth breathing would lead to defects in condylar development during adolescence, with the mechanism that chondrogenic differentiation of condylar mesenchymal stem cells was inhibited.…”
Section: The Impact Of Mouth Breathing On Dentofacial Healthmentioning
confidence: 99%
“…In an intermittent nasal congestion rat model, there was a significant reduction in the thickness of the hyperplasia layer as well as the hypertrophic layer of condylar joint, which suggested that the development of the temporomandibular joint was also influenced by oral breathing habits ( 63 ). A previous randomized controlled trial ( 64 ) established another bilateral rat model of intermittent nasal congestion, and it found that mouth breathing would lead to defects in condylar development during adolescence, with the mechanism that chondrogenic differentiation of condylar mesenchymal stem cells was inhibited.…”
Section: The Impact Of Mouth Breathing On Dentofacial Healthmentioning
confidence: 99%
“…Altered mechanical stresses on the joint due to mouth breathing may impact condylar development. 5 Mechanical pressure alters signalling in chondrocytes, affecting cartilage maintenance, degradation, and regeneration. This plays a crucial role in the pathogenesis of osteoarthritis.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] A close relationship exists between excessive loads and TMJOA.Altered mechanical stresses on the joint due to mouth breathing may impact condylar development. 5 Mechanical pressure alters signalling in chondrocytes, affecting cartilage maintenance, degradation,…”
mentioning
confidence: 99%
“…MB is considered to cause growth disturbance in the structures of the craniofacial complex [ 17 , 19 , 26 , 28 ]. Recent experimental studies suggested that MB impairs the development of TMJ in early stages [ 18 , 29 ]. Based on these, the authors hypothesized that individuals with MB may tend to have TMD signs/symptoms more commonly and there can be a link between MB and TMD.…”
Section: Introductionmentioning
confidence: 99%